Creative That Sells: How Advertising Execution Affects Sales. Issue 1 (2nd January 2016) - Hartnett, Nicole; Kennedy, Rachel; Sharp, Byron; Greenacre, Luke
Abstract : Advertising creative is widely accepted as critical to advertising success. However, generalizations of what works in applied settings across different conditions are few. The present study replicates the seminal work of Stewart and Furse(1986), who investigated the effect of more than 150 creative devices on several copy-testing measures of advertising effectiveness. We replicate the analysis using the original codebook but examine the link to in-market, short-term sales effectiveness. We use a large sample of 312 television ads from several product categories aired in multiple countries. Our findings indicate that the codebook remains relevant for characterizing current advertising practices but many of the creative devices found most (or least) effective differ to those from the original study. Similar to Stewart and Furse(1986), no single creative device can do much alone to explain sales effectiveness. There is no one simple cookbook for making sales effective advertising, though such research offers some important guidelines.